Prism adaptation combined with eye movement training for unilateral spatial neglect after stroke: Study protocol for a single-blind prospective, randomized controlled trial - Yang, Yu-xuan; Wang, Ling-ling; Du, Juan; Luo, Yao-min; Xie, Yu-lei; Zhang, Bo; Zhang, Han (Frontiers in Neurology, 2023)
Background Unilateral spatial neglect (USN) is a complex neurological syndrome that often reduces rehabilitation outcomes, prolongs patients' hospital stays, and decreases their quality of life. However, the current therapies for USN have varying efficacy. We will explore a new treatment option that combines prism adaptation (PA) with eye movement training (EMT) for the treatment of USN after stroke. Methods We will conduct a single-blind, prospective, randomized controlled trial to assess the efficacy of the combined intervention (PA & EMT) on USN in an inpatient rehabilitation setting. The study aims to recruit 88 patients with USN after an ischemic or hemorrhagic stroke. Participants will be randomly assigned to the following four groups: (1) PA group (n = 22), (2) EMT group (n = 22), (3) PA and EMT group (n = 22), and (4) control group (n = 22). All groups will receive 10 sessions of interventions over 2 weeks, 5 times per week. Blinded assessors will conduct a baseline assessment, a post-intervention assessment, and a follow-up assessment (2 weeks post-intervention). The primary outcome measure will use the Behavioral Inattention Test-Conventional Subset (BIT-C) and Catherine Bergego Scale (CBS) to assess the levels of USN. Secondary outcome measures will assess the patient's ability to perform activities of daily living using the Modified Barthel Index (MBI). Patients who completed all treatment and assessment sessions will be included in the final analysis. Discussion This study will explore the effects of 10 sessions of combined interventions (PA & EMT) on USN and functional capacity. This study has the potential to identify a new, evidence-based treatment option and provide new ideas for the treatment of USN. Ethics and dissemination The study protocol has been approved by the Nanchong Central Hospital. Written informed consent will be obtained from all the participants. The results of this study will be disseminated to the public through scientific conferences and a peer-reviewed journal. Trial registration ChiCTR, ChiCTR2100049482. Registered on 2 August 2021, http://www.chictr.org.cn/showproj.aspx?proj=130823.